Luteolin-Induced Activation of Mitochondrial BKCa Channels: Undisclosed Mechanism of Cytoprotection - Rafał P. Kampa; Lorenzo Flori; Aleksandra Sęk; Jacopo Spezzini; Simone Brogi; Adam Szewczyk; Vincenzo Calderone; Piotr Bednarczyk; Lara Testai (MDPI AG, 2022)
Luteolin (LUT) is a well-known flavonoid that exhibits a number of beneficial properties. Among these, it shows cardioprotective effects, as confirmed by numerous studies. However, its effect on mitochondrial potassium channels, the activation of which is related to cytoprotection, as well as on heart ischemia/reperfusion (I/R) damage prevention, has not yet been investigated. The large conductance calcium-regulated potassium channel (mitoBKCa) has been identified in both the mitochondria of the vascular endothelial cells, which plays a significant role in the functioning of the cardiovascular system under oxidative stress-related conditions, and in the mitochondria of cardiomyocytes, where it is deeply involved in cardiac protection against I/R injury. Therefore, the aim of this study was to explore the role of the mitoBKCa channel in luteolin-induced cytoprotection. A number of in vitro, in vivo, ex vivo and in silico studies have confirmed that luteolin activates this channel in the mitochondria of cardiomyocytes and endothelial cells, which in turn leads to the protection of the endothelium and a significant reduction in the extent of damage resulting from myocardial infarction, where this effect was partially abolished by the mitoBKCa channel blocker paxilline. In conclusion, these results suggest that luteolin has cardioprotective effects, at least in part, through the activation of the mitoBKCa channel, shedding light on a new putative mechanism of action.